1975
DOI: 10.1080/00049537508255241
|View full text |Cite
|
Sign up to set email alerts
|

An integrative progress report on informational control in humans: Some laboratory findings and methodological claims

Abstract: When noxious unavoidable events (e.g., shocks) are signalled (e.g., by a 5-sec. tone), it is widely believed that there is informational control (IC) in the sense that signalling reduces perceived event noxiousness; the IC mechanism arises through signal-elicited preparatory anticipatory responses which reduce event noxiousness; there is a prefere,nce for signalled over unsignalled events (preference for signalling). Since these beliefs, though related, are different, the relevant evidence from the Toronto lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 37 publications
2
25
1
Order By: Relevance
“…Both Furedy andDoob (1971, p. 263) andMiller et al (1974, p. 273) have drawn attention to notions of "conditioned fear" and "conditioned aversion to the signal," respectively, notions which stem from the recognition that the signal may not have only beneficial effects and that there may, therefore, be factors which work against rmding a PSS phenomenon. The conditioned fear notion would suggest that fear, as a secondary drive, increases the impact or aversiveness of signaled shock, and thereby makes unsignaled shock preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Both Furedy andDoob (1971, p. 263) andMiller et al (1974, p. 273) have drawn attention to notions of "conditioned fear" and "conditioned aversion to the signal," respectively, notions which stem from the recognition that the signal may not have only beneficial effects and that there may, therefore, be factors which work against rmding a PSS phenomenon. The conditioned fear notion would suggest that fear, as a secondary drive, increases the impact or aversiveness of signaled shock, and thereby makes unsignaled shock preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a series of chi-square tests indicated that the proportions of subjects preferring signaled vs. unsignaled ues presentations did not differ significantly at any of the five intensity levels for either the airpuff or shock DeS. In view of the strength of belief in the PFS phenomenon documented by Furedy (1975), the present results are of interest in providing yet another failure to demonstrate this phenomenon even under conditions where ues modification is possible (i.e., in the airpuff subjects).…”
Section: The Ie Phenomenonmentioning
confidence: 99%
“…A review of evidence on IC in humans from the Toronto laboratory has indicated that the limits on IC are quite severe (Furedy, 1975). In brief summary, there was no evidence in these studies to support the occurrence of a PAR mechanism in such signal~licited anticipatory responses as the GSR, digital vasomotor response, and cardiac rate (Furedy, 1975, pp.…”
mentioning
confidence: 99%
See 2 more Smart Citations